A systematic review of anxiety across smoking stages in adolescents and young adults. (3rd July 2019) - Yan, Yunwei; Sun, Shuxia; Deng, Songyuan; Jiang, Jicheng; Duan, Fujiao; Song, Chunhua; Wang, Kaijuan; Zhang, Nan; Tian, Qingfeng; Nie, Wei
Abstract: Background : In adolescence and young adults, inconsistence of the association between anxiety and smoking remains to be investigated and clarified. The aim of this study is investigated and clarified the association between anxiety and smoking stages in adolescence and young adults. Methods: The data on the causal influence of anxiety on smoking in adolescents and young adults aged 14 to 25 years old was retrieved from electronic databases. Results: Nineteen of 668 articles were subjected to a systematic review. Definitional differences with respect to smoking stages constrained homogeneity across the nineteen analyzed reports. Anxiety appears to play a more consistent risk role for nicotine dependent (ND) smokers than for non-nicotine dependent (non-ND) regular or daily smokers. Anxious non-ND smokers are at higher risk to become nicotine dependent. Conclusions: A ununified definition of smoking stages is responsible for the production of inconsistent results. The analysis reinforced anxiety as a significant risk factor for smoking in one's lifetime. Anxious non-ND smokers are the key target for interventions aimed at preventing nicotine dependence and smoking-related health problems.